2022
DOI: 10.3390/ani12182399
|View full text |Cite
|
Sign up to set email alerts
|

Autoclaved Diet with Inactivated Spores of Bacillus spp. Decreased Reproductive Performance of Muc2−/− and Muc2+/− Mice

Abstract: Within barrier facilities, autoclaved diet and bedding are used for husbandry of laboratory rodents. Bacillus spp. are ubiquitous in nature and some of them are known as probiotics. Inactivation of the Bacillus spores and reduction of the diet nutritional value due to autoclavation could be especially critical for immunodeficient mice. We studied the effect of the autoclaved and non-autoclaved diets on the reproductive performance and the age of prolapse manifestation in Muc2−/− mice with impaired gut barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
0
1
0
1
Order By: Relevance
“…Strains of the Bacillus spp. isolated from the nonautoclaved diet and mice feces were not resistant to kanamycin [41][42] . In this regard, it was possible to count the titer of B. subtilis BS20 that the mice received with diet [46] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strains of the Bacillus spp. isolated from the nonautoclaved diet and mice feces were not resistant to kanamycin [41][42] . In this regard, it was possible to count the titer of B. subtilis BS20 that the mice received with diet [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus spp. are present in laboratory diets for animals and can influence reproductive rates [41][42] . It was found that adding spores B. subtilis BS20 to the nonautoclaved diet had a higher effect on restoring normal behavior in Muc2 +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Поскольку штамм B. subtilis BS20 стимулирует гуморальное звено иммунитета у мышей Muc2 -/-, возможно, это способствует развитию у них устойчивости к патогенным микроорганизмам и объясняет увеличение массы тела и продолжительности жизни. В предыдущих исследованиях показано, что мыши Muc2 -/при кормлении неавтоклавированным кормом, содержащим несколько видов представителей рода Bacillus, характеризовались лучшим репродуктивным индексом, более поздним появлением пролапса прямой кишки и высоким содержанием Т-хелперов в селезёнке, по сравнению с физиологическими и иммунологическими показателями мышей, получавших автоклавированный корм, содержащий инактивированные споры бактерий [26]. Добавление в корм штамма B. subtilis DE111 способствует увеличению уровня регуляторных Т-клеток и Т-хелперов, наряду со снижением содержания Т-киллеров [23].…”
Section: Discussionunclassified
“…led to an increased incidence of intestinal inflammation due to alterations in the gut microbiome. Additionally, a decline in fertility was observed [ 62 ]. Table 2 provides a comprehensive overview of the medical and agricultural applications of B. amyloliquefaciens .…”
Section: The Importance and Applications Of The Bacillus Am...mentioning
confidence: 99%